Ramifications of the Hampton Court Conference in the Dioceses, 1603–1609 - Fincham, K. C. (The journal of ecclesiastical history, 1985)
We finding (right dread and soveraigne Lord), in the sacred records of God that the most worthy kings set over his people sanctifyed the entrance of their raigne with clensing the house of God from all idolatry and superstition and reforming the ministers thereof, according to the order appointed by God; the safest and surest way to establish the thrones of kings to themselves and their posterity. And we acknowledging with all thankfulnes to God that he hath touched your royall hart with a true love unto his sanctuarie and raysed you up as another Josiah even to pull down all the high places and to breake in peeces all the strange altars that remaine yet in Israell (for we must acknowledg as the truth that many of us and of the people have not yet prepared our harts to the God of our fathers) ar moved in those respects (most noble king) as remembrancers of the Lord to crie with our hart and voice for the effecting herof.